Subtract. (3×2 + 7) – (3x – 2) A. 3×2 – 3x+ 9 B. 3×2 – 3x + 5 C. 1×2 + 5 D. 1×2 + 9

Question

Subtract.
(3×2 + 7) – (3x – 2)
A. 3×2 – 3x+ 9
B. 3×2 – 3x + 5
C. 1×2 + 5
D. 1×2 + 9

in progress 0
Sapo 3 years 2021-08-05T20:20:49+00:00 2 Answers 8 views 0

Answers ( )

    0
    2021-08-05T20:22:09+00:00

    Answer:

    The answer is A.

    Step by step explanation:

    =(32+7)−(3−2)

    =(32+7)−3-2

    =32+7−3+2

    =32+9−3

    =32−3+9

    0
    2021-08-05T20:22:20+00:00

    Answer:

    A. 3×2 – 3x + 9

    Step-by-step explanation:

    * means multiplied

    (3×2 + 7) – (3x – 2)

    – (3x – 2) is really -1 * (3x – 2)

    so

    -1 * (3x – 2)

    is

    -3x + 2

    so

    (3×2 + 7) – (3x – 2) =

    (3×2 + 7) – 3x + 2 =

    3×2 – 3x + 9

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )